The treatment of sex offenders with developmental disabilities: a practice workbook - Lindsay, William R. (Wiley-Blackwell, 2009)
Introduction to offenders, sex offenders, and abusers with intellectual disability -- Assessment of offence related issues -- Risk assessment -- Treatment of inappropriate sexual behaviour -- Theories of sexual offending and intellectual disability -- A theory for the sex offence process and a model for treatment in offenders with intellectual disabilities -- Introduction to the treatment programme -- Promoting motivation -- Induction, setting the rules, explaining the modules -- Offence disclosure and accounts -- Allocating offenders to pathways -- Cognitive distortions and attitudes -- Problem solving scenarios and exercises which challenge cognitive distortions -- Personal physical and sexual abuse -- The cycle of offending -- Victim awareness and empathy -- Use of pornography and dealing with sexual fantasy -- Attachments and relationships -- Lifestyle change and preventing relapse -- Evaluation of progress